Improving economic development and sustainability: Macroeconomic Impact of Gender Diversity in Board Composition for European Economies - Vavura, Nicolae Marius; Matei, Gina; Firican, Diana-Andreea (Technium Social Sciences Journal, 2025)
Following the recent focus of the European Union on gender diversity with the imposition of EU-wide diversity quotas on listed company boards of directors, this paper aims to explore the potential macroeconomic impact of this regulation. The paper conducts several stages of econometric analysis meant to isolate a statistically valid effect that diversity can have upon a country’s macroeconomic performance, starting from the premise that there are indicators that are “close” enough to the actual economy to capture an effect that may be due to diversity changes, especially if they are related to the sustainability performance of that economy. Utilizing resource productivity as such a macroeconomic indicator, the paper successfully shows that there is a positive, significant and statistically relevant im-pact that gender diversity in board composition can have upon a country’s economy as a whole, within modelling limits. Further on, only seven countries out of 29 analyzed, individually exhibit statistically relevant positive influences of gender diversity upon eco-nomic performance, while a panel data analysis concludes that the EU can potentially expect a 0.7 increase in its countries’ resource productivity index for each percentage point increase in diversity, within conceptual limits.